Soviet Leaders in Western Media Space - I. V. Suslov; D. S. Artamonov; A. R. Faizliev (Научный диалог, 2022)
The results of the analysis of the USSR image in Western social media are presented. The novelty of the study lies in the use of the Global Database of Events, Language, and Tone in the analysis of the image of Soviet leaders in the Euro-Atlantic press. A review of messages that mention the names of the leaders of the USSR from January 1, 2017 to the present in the Western press has been completed. It is proved that the overall emotional tone of the narrative about the Soviet leaders in Western media is extremely negative. It is noted that French and German journalists, in comparison with Anglo-Saxon ones, more often write about Soviet history in a positive context. It is emphasized that the differences correlate with the quality of relations between Western countries and Russia, as well as the prospects for their improvement. It is shown that journalists, discussing the Soviet leaders, raise existential questions that are important for the Euro-Atlantic mass consciousness. The relevance of the study is due to the fact that the growth of media interest in the stories of rapprochement between the USSR and the West, as well as the emotionally positive transformation of the images of Soviet leaders in the media is considered as a condition and indicator of improving relations between Russia and the West.